Small dams also change the benthic macroinvertebrates community in rocky rivers - Mattos,Leticia de (2017)
Abstract Aim: Here we analyzed some basic ecological attributes (richness and density) of the benthic community in a stretch of a rocky river under the influence of a small dam of a meter in height, forming a small reservoir of run-of-river type. Methods Sediment samples were taken with a Petersen collector at three different periods and in three sites: upstream from the dam (site 1), close to the dam (site 2) and downstream from the dam (site 3). Organisms were separated in large groups and Chironomidae genera. Results The particle size analysis indicated that the sites 1 and 2 are dominated by fine sediments, in contrast to site 3, composed of medium and coarse sediments. A total of 23 taxa of benthic macroinvertebrate groups and 31 genera of Chironomidae were found. Richness and density were different among sampling sites, and for large groups and Chironomidae its attributes increased towards downstream, probably explained by the sediment composition and the originally lotic conditions in site 3, confirmed by all statistical analysis used. In the dam site (2) there was a richness decrease. Non metric multidimensional analysis showed a clear spatial separation of large groups of macroinvertebrates and chironomid genera between sampling sites, indicating that there are typical taxa of each spatial compartment. Canonical correspondence analysis correlated only rubble sediment with the abundance of large groups, and for Chironomidae genera only the granules type was correlationed, with two groups of taxa in the anlysis: one with sites 1 and 2, and other with site 3. Conclusions Even very small dams in rocky rivers as in the present study alter the environmental variables and ecological attributes of benthic macroinvertebrates.